Computer organization and design : the hardware/software interface - Patterson, David A.; Hennessy, John L. (Morgan Kaufmann series in computer architecture and design.)
"Presents the fundamentals of hardware technologies, assembly language, computer arithmetic, pipelining, memory hierarchies and I/O"--Provided by publisher.